Consumption of Katuk Leaf–Fortified Catfish Nuggets Improves Breast Milk Production - Nurul Pujiastuti; Nur Rahman; Sugeng Iwan Setyobudi (Health Notions, 2026)
Exclusive breastfeeding remains a global public health priority, yet many mothers experience insufficient breast milk production due to physiological, behavioral, and psychosocial factors. Katuk leaves (Sauropus androgynus) are traditionally recognized in Indonesia for their lactogenic properties, while catfish (Clarias batrachus) provides high‑quality protein and essential fatty acids that support maternal nutritional status. Integrating these ingredients into a functional food product may offer a practical dietary approach to enhance lactation. This study aimed to to describe changes in breast milk production among lactating mothers following the consumption of katuk leaf–fortified catfish nuggets over a two‑week period. A descriptive case study was conducted in Martopuro Village, Pasuruan Regency, during August 2025. Three purposively selected lactating mothers with infants aged 0–6 months consumed 100 g of fortified nuggets every two days for 14 days. Breast milk volume was measured using a standardized graduated pump container at baseline and post‑intervention. Maternal perceptions of lactation were assessed using a five‑item questionnaire adapted from validated lactation assessment tools. Data were analyzed descriptively to identify individual trends. All participants demonstrated an upward trend in breast milk production, reflected in increased expressed milk volume and improved maternal lactation perception scores. These findings align with the biological plausibility of katuk leaf phytochemicals; such as flavonoids, saponins, and phytosterols which may stimulate prolactin pathways and enhance mammary gland function. The nutritional contribution of catfish protein and essential fatty acids may further support milk synthesis. However, several confounding factors were identified, including high baseline hydration, increased breastfeeding frequency, and potential placebo effects, limiting the interpretability of the observed improvements. In conclusion, katuk leaf–fortified catfish nuggets show potential as an acceptable functional food to support lactation, but the descriptive nature of this study and its very small sample size preclude causal inference. Larger randomized controlled trials with standardized controls and confounder monitoring are required to validate the efficacy of this formulation.Keywords: katuk leaves; Sauropus androgynus; catfish; functional food; lactation; breast milk production